2014
DOI: 10.1002/pits.21778
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Socio-Motivational Relationships in the Interplay of Perceived Stress, Neuroticism, and Test Anxiety Among Adolescent Students

Abstract: In this study, we examined whether socio-motivational relationships, such as student-student relationships (SSR) and teacher-student relationships (TSR), as well as peers as positive motivators (PPM) and teachers as positive motivators (TPM), would mediate the association of both perceived stress and neuroticism with test anxiety in 1,088 German students from grades seven and eight. Results from structural equation modeling revealed that a high quality of SSR mediated the relationship between neuroticism and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 122 publications
5
32
0
4
Order By: Relevance
“…The present finding of a negative relation between these variables should be interpreted with caution considering that only approximately 4% of the variance was accounted for in this study. These results support Hoferichter et al's () suggestion that being socially connected with peers mitigates the effects of stressful situations and cultivates healthy socio‐emotional development. Additionally, positive social connections encourage the disclosure of emotions to peers and this may contribute to lessened test anxiety (Strahan, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present finding of a negative relation between these variables should be interpreted with caution considering that only approximately 4% of the variance was accounted for in this study. These results support Hoferichter et al's () suggestion that being socially connected with peers mitigates the effects of stressful situations and cultivates healthy socio‐emotional development. Additionally, positive social connections encourage the disclosure of emotions to peers and this may contribute to lessened test anxiety (Strahan, ).…”
Section: Discussionsupporting
confidence: 89%
“…Positive social connections may be negatively related to test anxiety, especially considering social connectedness has a positive impact on student engagement and belonging in education (Graunke et al, ). Hoferichter, Raufelder, and Eid () found that positive student–student relationships showed significant negative and mediating effects on test anxiety. Positive peer social connectedness fosters the capacity for the test taker to reduce perceived negative interpersonal implications of doing poorly on tests and may effectively lessen test anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a previous study by Hoferichter et al. () has found a positive association between neuroticism and socio‐motivational TSR, suggesting that neurotic students going through adolescence may be more inclined to identify a role model in their teachers than in their parents (Raufelder, ) or that they may seek a social referent in teachers (Hughes, Cavell, & Willson, ), providing support and security (Harter, ; Wentzel, ).…”
Section: Emotions In Teacher–student Relationshipsmentioning
confidence: 91%
“…Adolescents’ relationships with their teachers are complex in nature. On an institutional level, teachers instruct students and provide feedback regarding their academic performance (Becker & Luthar, ; Pianta, Hamre, & Stuhlman, ; Radel, Sarrazin, Legrain, & Wild, ; Wentzel, ), thereby acting as positive motivators (Hoferichter, Raufelder, & Eid, ; Raufelder, Drury, Jagenow, Hoferichter, & Bukowski, ). In contrast, on an interpersonal level, teachers communicate their more general approval or disapproval of the student as a person (Birch & Ladd, ), which can affect students’ sense of identity (Alerby & Hertting, ; Birch & Ladd, ; Jennings & Greenberg, ).…”
Section: Emotions In Teacher–student Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation